Learning to Live with Ticks? The Role of Exposure and Risk Perceptions in Protective Behaviour Against Tick-Borne Diseases - Dataset for study of the Role of Exposure and Risk Perceptions in Protective Behaviour Against Tick-Borne Diseases - Slunge, Daniel (University of Gothenburg, 2018)
The purpose of this study is to analyse the role of risk perceptions and exposure for protective behaviour against tick bites and the related diseases Lyme borreliosis (LB) and tick-borne encephalitis (TBE), both of which are growing health concerns. We use data from a national survey in Sweden with respondents in geographical areas with substantial differences in both abundance of ticks and incidence of LB and TBE. We find that the share of respondents who frequently use protective clothing (64%), perform tick checks (63%) or avoid tall grass while in areas with ticks (48%) is relatively high. However, the use of protective measures is uneven and a considerably lower share tuck their trousers into their socks (18%), use repellent against ticks (16%) or use a combination of protective measures. Thirty-one per cent of the respondents report one or more tick bites in the last year and 68% report one or more lifetime tick bites, indicating that it is difficult to protect oneself from tick bites. There is a strong positive association between exposure and checking the skin for ticks, but exposure is only weakly associated with other protective measures. Tick bites are perceived as a serious health risk by as many as 43% of the respondents. The perception that a single tick bite is serious is negatively associated with actual exposure to ticks, while the opposite is true for the perception that tick bites constitute a serious lifetime health risk. This indicates a learning effect in relation to risk perceptions and the performance of tick checks, but not in relation to other protective measures. Recommendations include informing people of the risks associated with tick bites, the efficacy of various protective measures and the importance of combining multiple types of protection. Given the high exposure to tick bites, the growing incidence of TBE and LB, and the difficulties in preventing tick bites, other preventive measures should be further discussed, including vaccination programmes.

Purpose:

To analyse the role of risk perceptions and exposure for five protective measures against tick bites and the related diseases tick-borne encehalitis (TBE) and Lyme borreliosis (LB).

The dataset contains the variables used in the study "Learning to Live with Ticks? The Role of Exposure and Risk Perceptions in Protective Behavior Against Tick-Borne Diseases", by Slunge and Boman. The questionnaire about Ticks, TBE and Borrelia contains additional questions that are not included in this material. Data is available for download in SPSS and STATA format.

Vi analyserar vilken roll riskuppfattningar och riskexponering spelar för fem olika sätt att skydda sig mot fästingbett, TBE och borrelia. Vi finner ett starkt positivt samband mellan exponering och att undersöka kroppen för fästingar, men inga eller svaga samband mellan exponering och att använda skyddande kläder, ha strumporna utanpå byxorna, använda fästingmedel eller undvika högt gräs eller andra områden där fästingar kan förekomma.

Syfte:

Att analysera vilken roll riskuppfattningar och riskexponering spelar för fem olika sätt att skydda sig mot fästingbett, TBE och borrelia.

Datasetet innehåller de variabler som använts i studien "Learning to Live with Ticks? The Role of Exposure and Risk Perceptions in Protective Behaviour Against Tick-Borne Diseases ", av Slunge och Boman. Enkäten om fästingar, TBE och Borrelia innehåller ytterligare frågor som inte ingår i detta underlag. Data finns tillgängligt för nedladdning i SPSS och STATA format.
Kan vi lära oss att leva med fästingar? En studie av riskuppfattning och beteende kopplat till fästingburna sjukdomar - Dataset för studie av riskuppfattning och beteende kopplat till fästingburna sjukdomar
Keywords: Ticks; Fästingar; Tick-Borne Diseases; Fästingburna sjukdomar; Borrelia Infections; Borreliainfektioner; Encephalitis, Tick-Borne; Fästingburen hjärninflammation; TBE; TBE; risk perception; riskuppfattning; protective behaviour; skyddsbeteende; ECONOMICS; EKONOMI; HEALTH; HÄLSA; NATURAL ENVIRONMENT; NATUR OCH MILJÖ; Medical and Health Sciences; Medicin och hälsovetenskap; Social Sciences; Samhällsvetenskap